MITIGATING QR-PHISHING RISKS IN INDONESIAN DIGITAL PAYMENTS THROUGH SECURITY BEHAVIOR INTENTIONS SCALE - Baottong, Mozes Haryanto; Kausar, Al; Taufiq, Muhammad Imam; Krisnanto, Budhi (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze the role of user awareness in mitigating the risk of quishing (QR phishing) in QR code-based digital transactions. The primary focus of this study is to examine whether user awareness acts as a mediating variable that strengthens the influence of user behaviors, such as password management, software updates, and device security practices, on quishing risk mitigation. This study used a quantitative approach using the Structural Equation Modeling (SEM) method to analyze the relationship between variables. Data was collected through an online survey involving 400 active QR code users in Indonesia. The results indicate that user awareness plays a significant role in enhancing quishing risk mitigation, both directly and through influencing user behavior. Good password management, regular software updates, and good device security practices have a positive effect on quishing risk mitigation, and this influence is further strengthened by user awareness. Furthermore, the results also reveal that increased user awareness can directly reduce their vulnerability to quishing attacks. The practical implication of these findings is the importance of digital security education programs that can increase user awareness of Quishing threats. Financial institutions, especially Bank Indonesia, and digital payment service providers can utilize these results to design policies that focus on increasing digital security awareness for users. Academically, this study adds to the understanding of the relationship between user awareness, user behavior, and Quishing risk mitigation in the context of QR Code-based digital payment systems, as well as contributing to the cybersecurity literature in the digital transaction sector.